Lithium iron phosphate material as well as preparation method and application thereof
By double-layer coating of lithium iron phosphate material with silver doping and modified polypyrrole, a continuous conductive network is formed, which solves the problems of low discharge capacity and poor cycle performance of lithium iron phosphate material, achieves improvement of electronic conductivity and cycle stability, and enhances the overall performance of lithium-ion batteries.
Patent Information
- Application Number
- CN202511138298.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-14
- Publication Date
- 2025-09-12
- Estimated Expiration
- 2045-08-14
AI Technical Summary
Existing lithium iron phosphate materials have low discharge specific capacity and poor cycle performance, which affects the overall performance of lithium-ion batteries.
A double-layer coated silver-doped lithium iron phosphate material is used, and a continuous conductive network is formed through the coating of a carbon layer and modified polypyrrole, which improves electronic conductivity, buffers volume changes during charging and discharging, and enhances cycle stability.
The electronic conductivity and cycle stability of lithium iron phosphate materials are significantly improved, thereby improving the overall performance and service life of the battery.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium-ion batteries, and in particular to a lithium iron phosphate material and a preparation method and application thereof. Background Art
[0002] In the prior art, lithium-ion batteries, as an important energy storage device, have been widely used in electronic devices, electric vehicles, and large-scale energy storage systems. Lithium iron phosphate, as an important lithium-ion battery positive electrode material, has attracted widespread attention due to its advantages such as non-toxicity, environmental protection, and low cost. However, traditional lithium iron phosphate materials have certain problems: first, their discharge specific capacity is relatively low, which limits the energy density of the battery; second, the cycle stability of lithium iron phosphate materials needs to be improved. During the charge and discharge process, the lithium iron phosphate material will undergo volume changes, resulting in poor cycle performance and affecting the service life of the battery. Therefore, the development of a lithium iron phosphate material and its preparation method and application are of great practical significance and application value for improving the overall performance of lithium-ion batteries. Summary of the Invention
[0003] In order to overcome the above technical problems, the purpose of the present invention is to provide a lithium iron phosphate material and its preparation method and application, which solves the problem that the existing lithium iron phosphate material has relatively low discharge capacity, poor cycle performance, and seriously affects the overall performance of lithium-ion batteries.
[0004] The purpose of the present invention can be achieved through the following technical solutions: In a first aspect, the present application provides a lithium iron phosphate material, comprising the following components in parts by weight: Double-layer coating: 8-10 parts of silver-doped lithium iron phosphate, 1-1.2 parts of binder, 1-1.5 parts of conductive agent and 15-17 parts of solvent; The double-layer coated silver-doped lithium iron phosphate is prepared by the following steps: Step s1: lithium carbonate, ferric nitrate nonahydrate, ammonium dihydrogen phosphate and citric acid solution are added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen is introduced for protection. The mixture is stirred and reacted at a temperature of 25-30° C. and a stirring rate of 200-300 r / min for 20-30 minutes. Silver nitrate is then added and the stirring reaction is continued for 20-30 minutes. The pH is then adjusted to 8.5-9.5 with ammonia water, and the stirring reaction is continued for 2-4 hours. After the reaction is completed, the reaction product is allowed to stand and age for 10-15 hours, and then placed in a vacuum drying oven and dried at a temperature of 80-85° C. for 2-3 hours to obtain a silver-doped lithium iron phosphate precursor; Step s2: adding a silver-doped lithium iron phosphate precursor, glucose and deionized water to a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, introducing nitrogen protection, stirring and reacting at a temperature of 25-30°C and a stirring rate of 200-300 r / min for 1-2 hours, then spray-drying to a particle size of ≤2 μm, then placing in a tube furnace, introducing argon protection, and heating to 350-360°C at a heating rate of 8-10°C / min and sintering for 3-4 hours, then heating to 650-750°C and sintering for 6-8 hours, and then cooling with the furnace to obtain carbon-coated silver-doped lithium iron phosphate; Step s3: Pyrrole, potassium tert-butoxide, 5-chloro-2-nitrotrifluorotoluene and anhydrous ether are added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred and reacted at a temperature of 25-30° C. and a stirring rate of 200-300 r / min for 30-40 minutes, and then the temperature is raised to reflux and the stirring reaction is continued for 7-8 hours. After the reaction is completed, the reaction product is cooled to room temperature and then poured into ice water. The organic phase is rotary evaporated to remove the solvent, and then placed in a vacuum drying oven and dried at a temperature of 50-55° C. for 3-4 hours. Then, the product is purified by silica gel column chromatography with an eluent to obtain modified pyrrole; Step s4: Add anhydrous ferric chloride and ethanol solution to a three-necked flask equipped with an agitator and a thermometer, stir and react for 30-50 minutes at a temperature of 0-5°C and a stirring rate of 200-300r / min, then add carbon-coated silver-doped lithium iron phosphate and continue stirring and reacting for 20-30 minutes, then add modified pyrrole and continue stirring and reacting at a temperature of 25-30°C for 15-20 hours. After the reaction is completed, centrifuge the reaction product, wash the precipitate with anhydrous methanol and distilled water 2-3 times in sequence, and then place it in a vacuum drying oven and dry it at a temperature of 60-65°C for 4-5 hours to obtain a double-layer coated silver-doped lithium iron phosphate.
[0005] As a further embodiment of the present invention, the lithium carbonate, ferric nitrate nonahydrate, ammonium dihydrogen phosphate, citric acid solution and silver nitrate in step s1 are used in a ratio of 11-13 mmol: 10 mmol: 10 mmol: 50-60 mL: 0.1-0.5 g.
[0006] As a further solution of the present invention: the mass fraction of the citric acid solution in step s1 is 3-5%; the mass fraction of the ammonia water is 20-25%.
[0007] As a further solution of the present invention: the usage ratio of the silver-doped lithium iron phosphate precursor, glucose and deionized water in step s2 is 10g:1-7g:90-100mL.
[0008] As a further embodiment of the present invention: the amount ratio of pyrrole, potassium tert-butoxide, 5-chloro-2-nitrotrifluorotoluene and anhydrous ether in step s3 is 10 mmol: 10 mmol: 10 mmol: 60-70 mL As a further solution of the present invention: the eluent in step s3 is a mixture of petroleum ether and ethyl acetate in a volume ratio of 10-15:3.
[0009] As a further solution of the present invention: the usage ratio of the anhydrous ferric chloride, ethanol solution, carbon-coated silver-doped lithium iron phosphate and modified pyrrole in step s4 is 2.5-4.5 g: 70-80 mL: 5 g: 0.3-0.9 g.
[0010] As a further solution of the present invention: the volume fraction of the ethanol solution in step s4 is 50-60%.
[0011] In a second aspect, the present application provides a method for preparing a lithium iron phosphate material, comprising the following steps: Step 1: Weigh 8-10 parts of double-layer coated silver-doped lithium iron phosphate, 1-1.2 parts of binder, 1-1.5 parts of conductive agent and 15-17 parts of solvent according to weight and set aside; Step 2: Add the double-layer coated silver-doped lithium iron phosphate, a binder, a conductive agent and a solvent into a ball mill, and ball mill for 3-5 hours at a ball milling rate of 200-300 r / min to obtain a lithium iron phosphate material.
[0012] As a further solution of the present invention: the binder is Kynar Flex PVDF 2850-07.
[0013] As a further solution of the present invention: the conductive agent is conductive carbon black Super P.
[0014] As a further embodiment of the present invention: the solvent is N-methylpyrrolidone.
[0015] In a third aspect, the present application provides an application of the lithium iron phosphate material prepared by the preparation method of the lithium iron phosphate material in the positive electrode of a lithium ion battery.
[0016] Beneficial effects of the present invention: The present invention discloses a lithium iron phosphate material, a preparation method thereof, and an application thereof. The lithium iron phosphate material is obtained by ball-milling a double-layer coated silver-doped lithium iron phosphate, a binder, a conductive agent, and a solvent. The main raw material of the lithium iron phosphate material is the double-layer coated silver-doped lithium iron phosphate. The double-layer coated silver-doped lithium iron phosphate is composed of polypyrrole containing nitro and fluorine elements, a double-layer carbon coating, and silver-doped lithium iron phosphate. The double-layer coated silver-doped lithium iron phosphate can effectively improve the electronic conductivity of the lithium iron phosphate material, promote the rapid transmission of electrolyte ions, and significantly improve the cycle stability of the lithium iron phosphate material, thereby enhancing the electrochemical properties of the overall material, especially the cycle stability and rate performance, and greatly improving the comprehensive performance and service life of the battery.
[0017] In the process of preparing lithium iron phosphate material, a double-layer coated silver-doped lithium iron phosphate is first prepared, and lithium carbonate, ferric nitrate nonahydrate, and ammonium dihydrogen phosphate are used as raw materials, and silver nitrate is used as a doping substance to prepare a silver-doped lithium iron phosphate precursor. Then, glucose is used as a carbon source to treat the silver-doped lithium iron phosphate precursor, and a carbon layer is formed after sintering to achieve a primary coating to obtain carbon-coated silver-doped lithium iron phosphate. Then, pyrrole and 5-chloro-2-nitrotrifluorotoluene are reacted, and the secondary amine group on the pyrrole reacts with the chlorine atom on the 5-chloro-2-nitrotrifluorotoluene to obtain a modified pyrrole containing nitro and fluorine elements. Then, the modified pyrrole is used as a monomer for polymerization to form polypyrrole coated on the surface of the carbon-coated silver-doped lithium iron phosphate to achieve secondary coating and obtain a double-layer coated silver-doped lithium iron phosphate; silver doping can improve the electronic conductivity inside the lithium iron phosphate material, and after being coated with a carbon layer, the lithium iron phosphate can be made A continuous conductive network is formed on the surface of the material, connecting the active particles, effectively reducing the contact resistance between the particles and further enhancing its conductivity. After being coated with polypyrrole, it can buffer the volume change of lithium iron phosphate particles during the charge and discharge process, prevent the particles from breaking and pulverizing, and thus improve the cycle stability of the lithium iron phosphate material. At the same time, the pyrrole ring in polypyrrole gives polypyrrole excellent conductive properties, and the nitrogen atom in the nitro group has a strong electron-accepting ability. During the charge and discharge process, the nitro group can achieve rapid electron transmission through a reversible redox reaction, further enhancing the conductive properties of polypyrrole. Moreover, the introduction of fluorine atoms in its molecular structure can improve the chemical stability of polypyrrole, enabling it to resist erosion and oxidation by the electrolyte, thereby further significantly improving the conductive properties and cycle stability of the lithium iron phosphate material, giving it excellent electrochemical properties. DETAILED DESCRIPTION
[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts shall fall within the scope of protection of the present invention.
[0019] Example 1: This embodiment is a method for preparing a lithium iron phosphate material, comprising the following steps: Step A1: 11 mmol of lithium carbonate, 10 mmol of ferric nitrate nonahydrate, 10 mmol of ammonium dihydrogen phosphate, and 50 mL of a 3% by mass citric acid solution were added to a three-necked flask equipped with a stirrer, a thermometer, and a gas guide tube. Nitrogen was introduced for protection, and the mixture was stirred at 25° C. and a stirring rate of 200 r / min for 20 minutes. Then, 0.1 g of silver nitrate was added and the stirring reaction was continued for 20 minutes. The pH was then adjusted to 8.5 with 20% by mass aqueous ammonia, and the stirring reaction was continued for 2 hours. After the reaction was completed, the reaction product was allowed to stand for 10 hours, and then placed in a vacuum drying oven and dried at 80° C. for 2 hours to obtain a silver-doped lithium iron phosphate precursor; Step A2: 10 g of silver-doped lithium iron phosphate precursor, 1 g of glucose, and 90 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer, and a gas guide tube, and nitrogen was introduced for protection. The mixture was stirred at a temperature of 25° C. and a stirring rate of 200 r / min for 1 hour, and then spray-dried to a particle size of ≤2 μm. The mixture was then placed in a tube furnace, argon was introduced for protection, and the temperature was increased to 350° C. at a heating rate of 8° C. / min and sintered for 3 hours. The temperature was then increased to 650° C. and sintered for 6 hours. The mixture was then cooled in the furnace to obtain carbon-coated silver-doped lithium iron phosphate; Step A3: 10 mmol of pyrrole, 10 mmol of potassium tert-butoxide, 10 mmol of 5-chloro-2-nitrotrifluorotoluene, and 60 mL of anhydrous ether were added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube, and a reflux condenser. The mixture was protected by nitrogen and stirred at 25° C. and a stirring rate of 200 r / min for 30 minutes. The mixture was then heated to reflux and stirred for 7 hours. After the reaction, the reaction product was cooled to room temperature and poured into ice water. The organic phase was rotary evaporated to remove the solvent and then placed in a vacuum drying oven for drying at 50° C. for 3 hours. The mixture was then purified by silica gel column chromatography using a mixture of petroleum ether and ethyl acetate in a volume ratio of 10:3 as an eluent to obtain the modified pyrrole. Step A4: 2.5 g of anhydrous ferric chloride and 70 mL of a 50% volume fraction ethanol solution were added to a three-necked flask equipped with a stirrer and a thermometer, and the mixture was stirred at 0°C and a stirring rate of 200 r / min for 30 minutes. Then, 5 g of carbon-coated silver-doped lithium iron phosphate was added and the stirring reaction was continued for 20 minutes. Then, 0.3 g of modified pyrrole was added and the mixture was heated to 25°C and the stirring reaction was continued for 15 hours. After the reaction was completed, the reaction product was centrifuged, and the precipitate was washed twice with anhydrous methanol and distilled water in sequence, and then placed in a vacuum drying oven and dried at 60°C for 4 hours to obtain a double-layer coated silver-doped lithium iron phosphate; Step A5: Weigh 8 parts of double-layer coated silver-doped lithium iron phosphate, 1 part of a binder, 1 part of a conductive agent, and 15 parts of a solvent according to weight and set aside; the binder is Kynar Flex PVDF 2850-07; the conductive agent is conductive carbon black SuperP; and the solvent is N-methylpyrrolidone; Step A6: Add the double-layer coated silver-doped lithium iron phosphate, a binder, a conductive agent and a solvent into a ball mill, and ball mill for 3 hours at a ball milling rate of 200 r / min to obtain a lithium iron phosphate material.
[0020] Example 2: This embodiment is a method for preparing a lithium iron phosphate material, comprising the following steps: Step A1: 12 mmol of lithium carbonate, 10 mmol of ferric nitrate nonahydrate, 10 mmol of ammonium dihydrogen phosphate, and 55 mL of a 4% by mass citric acid solution were added to a three-necked flask equipped with a stirrer, a thermometer, and a gas guide tube. The mixture was protected by nitrogen and stirred at 28° C. and a stirring rate of 250 r / min for 25 minutes. 0.3 g of silver nitrate was then added and the mixture was stirred and reacted for 25 minutes. The pH was then adjusted to 9 with 22% by mass aqueous ammonia, and the mixture was stirred and reacted for 3 hours. After the reaction, the reaction product was allowed to stand and age for 12 hours, and then placed in a vacuum drying oven and dried at 82° C. for 2.5 hours to obtain a silver-doped lithium iron phosphate precursor. Step A2: 10 g of silver-doped lithium iron phosphate precursor, 4 g of glucose, and 95 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer, and a gas guide tube, and nitrogen was introduced for protection. The reaction was stirred at a temperature of 28° C. and a stirring rate of 250 r / min for 1.5 h, and then spray-dried to a particle size of ≤2 μm. The mixture was then placed in a tube furnace, argon was introduced for protection, and the temperature was increased to 355° C. at a heating rate of 9° C. / min and sintered for 3.5 h. The temperature was then increased to 700° C. and sintered for 7 h. The mixture was then cooled in the furnace to obtain carbon-coated silver-doped lithium iron phosphate; Step A3: 10 mmol of pyrrole, 10 mmol of potassium tert-butoxide, 10 mmol of 5-chloro-2-nitrotrifluorotoluene, and 65 mL of anhydrous ether were added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube, and a reflux condenser. The mixture was protected by nitrogen and stirred at 28° C. and a stirring rate of 250 r / min for 35 minutes. The mixture was then heated to reflux and stirred for 7.5 hours. After the reaction, the reaction product was cooled to room temperature and poured into ice water. The organic phase was rotary evaporated to remove the solvent and then placed in a vacuum drying oven for drying at 52° C. for 3.5 hours. The mixture was then purified by silica gel column chromatography using a mixture of petroleum ether and ethyl acetate in a volume ratio of 12:3 as an eluent to obtain the modified pyrrole. Step A4: 3.5 g of anhydrous ferric chloride and 75 mL of a 55% volume fraction ethanol solution were added to a three-necked flask equipped with a stirrer and a thermometer, and the mixture was stirred at a temperature of 3°C and a stirring rate of 250 r / min for 40 minutes. Then, 5 g of carbon-coated silver-doped lithium iron phosphate was added and the stirring reaction was continued for 25 minutes. Then, 0.6 g of modified pyrrole was added and the temperature was raised to 28°C and the stirring reaction was continued for 18 hours. After the reaction was completed, the reaction product was centrifuged, and the precipitate was washed twice with anhydrous methanol and distilled water in sequence, and then placed in a vacuum drying oven and dried at a temperature of 62°C for 4.5 hours to obtain a double-layer coated silver-doped lithium iron phosphate; Step A5: Weigh 9 parts of double-layer coated silver-doped lithium iron phosphate, 1.1 parts of a binder, 1.3 parts of a conductive agent, and 16 parts of a solvent in parts by weight and set aside; the binder is Kynar Flex PVDF 2850-07; the conductive agent is conductive carbon black Super P; and the solvent is N-methylpyrrolidone; Step A6: Add the double-layer coated silver-doped lithium iron phosphate, a binder, a conductive agent and a solvent into a ball mill, and ball mill for 4 hours at a ball milling rate of 250 r / min to obtain a lithium iron phosphate material.
[0021] Example 3: This embodiment is a method for preparing a lithium iron phosphate material, comprising the following steps: Step A1: 13 mmol of lithium carbonate, 10 mmol of ferric nitrate nonahydrate, 10 mmol of ammonium dihydrogen phosphate, and 60 mL of a 5% by mass citric acid solution were added to a three-necked flask equipped with a stirrer, a thermometer, and a gas guide tube. Nitrogen protection was introduced, and the mixture was stirred at a temperature of 30° C. and a stirring rate of 300 r / min for 30 minutes. Then, 0.5 g of silver nitrate was added and the stirring reaction was continued for 30 minutes. Then, the pH was adjusted to 9.5 with 25% by mass aqueous ammonia, and the stirring reaction was continued for 4 hours. After the reaction, the reaction product was allowed to stand and age for 15 hours, and then placed in a vacuum drying oven and dried at a temperature of 85° C. for 3 hours to obtain a silver-doped lithium iron phosphate precursor; Step A2: 10 g of silver-doped lithium iron phosphate precursor, 7 g of glucose, and 100 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer, and a gas guide tube, and nitrogen was introduced for protection. The reaction was stirred at a temperature of 30° C. and a stirring rate of 300 r / min for 2 h, and then spray-dried to a particle size of ≤2 μm. The mixture was then placed in a tube furnace, argon was introduced for protection, and the temperature was increased to 360° C. at a heating rate of 10° C. / min and sintered for 4 h. The temperature was then increased to 750° C. and sintered for 8 h. The mixture was then cooled in the furnace to obtain carbon-coated silver-doped lithium iron phosphate; Step A3: 10 mmol of pyrrole, 10 mmol of potassium tert-butoxide, 10 mmol of 5-chloro-2-nitrotrifluorotoluene, and 70 mL of anhydrous ether were added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube, and a reflux condenser. The mixture was protected by nitrogen and stirred at 30° C. and a stirring rate of 300 r / min for 40 minutes. The mixture was then heated to reflux and stirred for 8 hours. After the reaction, the reaction product was cooled to room temperature and poured into ice water. The organic phase was rotary evaporated to remove the solvent and then placed in a vacuum drying oven for drying at 55° C. for 4 hours. The mixture was then purified by silica gel column chromatography using a mixture of petroleum ether and ethyl acetate in a volume ratio of 15:3 as an eluent to obtain the modified pyrrole. Step A4: 4.5 g of anhydrous ferric chloride and 80 mL of a 60% volume fraction ethanol solution were added to a three-necked flask equipped with a stirrer and a thermometer, and the mixture was stirred at a temperature of 5 ° C and a stirring rate of 300 r / min for 50 minutes. Then, 5 g of carbon-coated silver-doped lithium iron phosphate was added and the stirring reaction was continued for 30 minutes. Then, 0.9 g of modified pyrrole was added and the temperature was raised to 30 ° C and the stirring reaction was continued for 20 hours. After the reaction was completed, the reaction product was centrifuged, and the precipitate was washed three times with anhydrous methanol and distilled water in sequence. Then, it was placed in a vacuum drying oven and dried at a temperature of 65 ° C for 5 hours to obtain a double-layer coated silver-doped lithium iron phosphate; Step A5: Weigh 10 parts of double-layer coated silver-doped lithium iron phosphate, 1.2 parts of a binder, 1.5 parts of a conductive agent, and 17 parts of a solvent in parts by weight and set aside; the binder is Kynar Flex PVDF 2850-07; the conductive agent is conductive carbon black Super P; and the solvent is N-methylpyrrolidone; Step A6: Add the double-layer coated silver-doped lithium iron phosphate, a binder, a conductive agent and a solvent into a ball mill, and ball mill for 5 hours at a ball milling rate of 300 r / min to obtain a lithium iron phosphate material.
[0022] Comparative Example 1: This comparative example is a method for preparing a lithium iron phosphate material, comprising the following steps: Step A1: 13 mmol of lithium carbonate, 10 mmol of ferric nitrate nonahydrate, 10 mmol of ammonium dihydrogen phosphate, and 60 mL of a 5% by mass citric acid solution were added to a three-necked flask equipped with a stirrer, a thermometer, and a gas guide tube. Nitrogen protection was introduced, and the mixture was stirred at a temperature of 30° C. and a stirring rate of 300 r / min for 30 minutes. The pH was then adjusted to 9.5 with 25% by mass aqueous ammonia, and the stirring reaction was continued for 4 hours. After the reaction was completed, the reaction product was allowed to stand for 15 hours, and then placed in a vacuum drying oven and dried at a temperature of 85° C. for 3 hours to obtain a lithium iron phosphate precursor; Step A2: 10 g of lithium iron phosphate precursor and 100 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer, and a gas guide tube, and nitrogen was introduced for protection. The mixture was stirred at a temperature of 30 ° C and a stirring rate of 300 r / min for 2 h, and then spray-dried to a particle size of ≤2 μm. The mixture was then placed in a tube furnace, argon was introduced for protection, and the temperature was increased to 360 ° C at a heating rate of 10 ° C / min and sintered for 4 h. The temperature was then increased to 750 ° C and sintered for 8 h. The mixture was then cooled in the furnace to obtain lithium iron phosphate; Step A3: Weigh 10 parts of lithium iron phosphate, 1.2 parts of a binder, 1.5 parts of a conductive agent, and 17 parts of a solvent in parts by weight and set aside; the binder is Kynar Flex PVDF 2850-07; the conductive agent is conductive carbon black Super P; and the solvent is N-methylpyrrolidone; Step A4: lithium iron phosphate, a binder, a conductive agent and a solvent are added into a ball mill, and ball milled for 5 hours at a ball milling rate of 300 r / min to obtain a lithium iron phosphate material.
[0023] Comparative Example 2: This comparative example is a method for preparing a lithium iron phosphate material, comprising the following steps: Step A1: 13 mmol of lithium carbonate, 10 mmol of ferric nitrate nonahydrate, 10 mmol of ammonium dihydrogen phosphate, and 60 mL of a 5% by mass citric acid solution were added to a three-necked flask equipped with a stirrer, a thermometer, and a gas guide tube. Nitrogen protection was introduced, and the mixture was stirred at a temperature of 30° C. and a stirring rate of 300 r / min for 30 minutes. The pH was then adjusted to 9.5 with 25% by mass aqueous ammonia, and the stirring reaction was continued for 4 hours. After the reaction was completed, the reaction product was allowed to stand for 15 hours, and then placed in a vacuum drying oven and dried at a temperature of 85° C. for 3 hours to obtain a lithium iron phosphate precursor; Step A2: 10 g of lithium iron phosphate precursor, 7 g of glucose and 100 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, and nitrogen was introduced for protection. The reaction was stirred at a temperature of 30 ° C and a stirring rate of 300 r / min for 2 hours, and then spray-dried to a particle size of ≤ 2 μm. Then, it was placed in a tube furnace, argon was introduced for protection, and the temperature was increased to 360 ° C at a heating rate of 10 ° C / min and sintered for 4 hours. Then, the temperature was increased to 750 ° C and sintered for 8 hours, and then cooled with the furnace to obtain carbon-coated lithium iron phosphate; Step A3: Weigh 10 parts of carbon-coated lithium iron phosphate, 1.2 parts of a binder, 1.5 parts of a conductive agent, and 17 parts of a solvent in parts by weight and set aside; the binder is Kynar Flex PVDF 2850-07; the conductive agent is conductive carbon black Super P; and the solvent is N-methylpyrrolidone; Step A4: adding carbon-coated lithium iron phosphate, a binder, a conductive agent and a solvent into a ball mill, and ball milling for 5 hours at a ball milling rate of 300 r / min to obtain a lithium iron phosphate material.
[0024] Comparative Example 3: This comparative example is a method for preparing a lithium iron phosphate material, comprising the following steps: Step A1: 13 mmol of lithium carbonate, 10 mmol of ferric nitrate nonahydrate, 10 mmol of ammonium dihydrogen phosphate, and 60 mL of a 5% by mass citric acid solution were added to a three-necked flask equipped with a stirrer, a thermometer, and a gas guide tube. Nitrogen protection was introduced, and the mixture was stirred at a temperature of 30° C. and a stirring rate of 300 r / min for 30 minutes. Then, 0.5 g of silver nitrate was added and the stirring reaction was continued for 30 minutes. Then, the pH was adjusted to 9.5 with 25% by mass aqueous ammonia, and the stirring reaction was continued for 4 hours. After the reaction, the reaction product was allowed to stand and age for 15 hours, and then placed in a vacuum drying oven and dried at a temperature of 85° C. for 3 hours to obtain a silver-doped lithium iron phosphate precursor; Step A2: 10 g of silver-doped lithium iron phosphate precursor, 7 g of glucose, and 100 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer, and a gas guide tube, and nitrogen was introduced for protection. The reaction was stirred at a temperature of 30° C. and a stirring rate of 300 r / min for 2 h, and then spray-dried to a particle size of ≤2 μm. The mixture was then placed in a tube furnace, argon was introduced for protection, and the temperature was increased to 360° C. at a heating rate of 10° C. / min and sintered for 4 h. The temperature was then increased to 750° C. and sintered for 8 h. The mixture was then cooled in the furnace to obtain carbon-coated silver-doped lithium iron phosphate; Step A3: Weigh 10 parts of carbon-coated silver-doped lithium iron phosphate, 1.2 parts of a binder, 1.5 parts of a conductive agent, and 17 parts of a solvent in parts by weight and set aside; the binder is Kynar Flex PVDF 2850-07; the conductive agent is conductive carbon black SuperP; and the solvent is N-methylpyrrolidone; Step A4: adding carbon-coated silver-doped lithium iron phosphate, a binder, a conductive agent and a solvent into a ball mill, and ball milling for 5 hours at a ball milling rate of 300 r / min to obtain a lithium iron phosphate material.
[0025] Comparative Example 4: This comparative example is a method for preparing a lithium iron phosphate material, comprising the following steps: Step A1: 13 mmol of lithium carbonate, 10 mmol of ferric nitrate nonahydrate, 10 mmol of ammonium dihydrogen phosphate, and 60 mL of a 5% by mass citric acid solution were added to a three-necked flask equipped with a stirrer, a thermometer, and a gas guide tube. Nitrogen protection was introduced, and the mixture was stirred at a temperature of 30° C. and a stirring rate of 300 r / min for 30 minutes. Then, 0.5 g of silver nitrate was added and the stirring reaction was continued for 30 minutes. Then, the pH was adjusted to 9.5 with 25% by mass aqueous ammonia, and the stirring reaction was continued for 4 hours. After the reaction, the reaction product was allowed to stand and age for 15 hours, and then placed in a vacuum drying oven and dried at a temperature of 85° C. for 3 hours to obtain a silver-doped lithium iron phosphate precursor; Step A2: 10 g of silver-doped lithium iron phosphate precursor, 7 g of glucose, and 100 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer, and a gas guide tube, and nitrogen was introduced for protection. The reaction was stirred at a temperature of 30° C. and a stirring rate of 300 r / min for 2 h, and then spray-dried to a particle size of ≤2 μm. The mixture was then placed in a tube furnace, argon was introduced for protection, and the temperature was increased to 360° C. at a heating rate of 10° C. / min and sintered for 4 h. The temperature was then increased to 750° C. and sintered for 8 h. The mixture was then cooled in the furnace to obtain carbon-coated silver-doped lithium iron phosphate; Step A3: 4.5 g of anhydrous ferric chloride and 80 mL of a 60% volume fraction ethanol solution were added to a three-necked flask equipped with a stirrer and a thermometer, and the mixture was stirred at a temperature of 5 ° C and a stirring rate of 300 r / min for 50 minutes. Then, 5 g of carbon-coated silver-doped lithium iron phosphate was added and the stirring reaction was continued for 30 minutes. Then, 0.9 g of pyrrole was added and the temperature was raised to 30 ° C and the stirring reaction was continued for 20 hours. After the reaction was completed, the reaction product was centrifuged, and the precipitate was washed three times with anhydrous methanol and distilled water in sequence. Then, it was placed in a vacuum drying oven and dried at a temperature of 65 ° C for 5 hours to obtain a double-layer coated silver-doped lithium iron phosphate; Step A4: Weigh 10 parts of double-layer coated silver-doped lithium iron phosphate, 1.2 parts of a binder, 1.5 parts of a conductive agent, and 17 parts of a solvent in parts by weight and set aside; the binder is Kynar Flex PVDF 2850-07; the conductive agent is conductive carbon black Super P; and the solvent is N-methylpyrrolidone; Step A5: Add the double-layer coated silver-doped lithium iron phosphate, a binder, a conductive agent and a solvent into a ball mill, and ball mill for 5 hours at a ball milling rate of 300 r / min to obtain a lithium iron phosphate material.
[0026] Performance Testing The lithium iron phosphate materials of Examples 1-3 and Comparative Examples 1-4 were coated on aluminum foil, which was then cut into discs with a diameter of 14 mm. The discs were then placed in a vacuum drying oven and dried at 120°C for 12 hours to obtain positive electrodes. CR2025 button batteries were assembled using the lithium sheet as the negative electrode, Celgard 2400 as the separator, and 1 mol / L LiPF6 (EC:DMC=1:1, v / v) as the electrolyte. The batteries were left to stand for 12 hours to test their performance.
[0027] The test results are shown in Table 1: Table 1: Test results of discharge capacity and cycle stability of lithium iron phosphate materials
[0028] Referring to the data in the above table, based on the comparison between Examples 1-3 and Comparative Examples 1-4, it can be seen that the lithium iron phosphate material of the present application has a high discharge specific capacity and excellent cycle stability, and exhibits good electrochemical performance.
[0029] Among them, according to the comparison between Example 3 and Comparative Example 1, it can be seen that the discharge capacity and cycle stability of the lithium iron phosphate material can be significantly improved after the lithium iron phosphate material is doped with silver, coated with a carbon layer and a modified polypyrrole double layer.
[0030] Among them, according to the comparison between Example 3 and Comparative Example 2, it can be seen that the discharge specific capacity and cycle stability of the lithium iron phosphate material can be significantly improved after the lithium iron phosphate material is doped with silver and coated with modified polypyrrole; according to the comparison between Comparative Example 1 and Comparative Example 2, it can be seen that the discharge specific capacity and cycle stability of the lithium iron phosphate material can be significantly improved after the lithium iron phosphate material is coated with a carbon layer.
[0031] Among them, according to the comparison between Example 3 and Comparative Example 3, it can be seen that the discharge specific capacity and cycle stability of the lithium iron phosphate material can be significantly improved after the lithium iron phosphate material is coated with modified polypyrrole; according to the comparison between Comparative Example 1 and Comparative Example 3, it can be seen that the discharge specific capacity and cycle stability of the lithium iron phosphate material can be significantly improved after the lithium iron phosphate material is doped with silver and coated with a carbon layer.
[0032] Among them, according to the comparison between Example 3 and Comparative Example 4, it can be seen that the discharge specific capacity and cycle stability of the lithium iron phosphate material can be significantly improved after the lithium iron phosphate material is coated with modified polypyrrole; according to the comparison between Comparative Example 1 and Comparative Example 4, it can be seen that the discharge specific capacity and cycle stability of the lithium iron phosphate material can be significantly improved after the lithium iron phosphate material is doped with silver, carbon layer and polypyrrole double layer coating.
[0033] Throughout this specification, references to terms such as "one embodiment," "example," or "specific example" indicate that the specific features, structures, materials, or characteristics described in conjunction with that embodiment or example are included in at least one embodiment or example of the present invention. In this specification, schematic representations of these terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in any one or more embodiments or examples.
[0034] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the described specific embodiments or replace them in similar ways. As long as they do not deviate from the invention or exceed the scope defined in this application, they should all fall within the scope of protection of the present invention.
Claims
1. A lithium iron phosphate material, characterized in that: It comprises the following components in parts by weight: Double-layer coating: 8-10 parts of silver-doped lithium iron phosphate, 1-1.2 parts of binder, 1-1.5 parts of conductive agent and 15-17 parts of solvent; The double-layer coated silver-doped lithium iron phosphate is prepared by the following steps: Step s1: lithium carbonate, ferric nitrate nonahydrate, ammonium dihydrogen phosphate, and citric acid solution are stirred for reaction, silver nitrate is added, the pH is adjusted with aqueous ammonia, and the stirring reaction is continued. After the reaction is completed, the reaction product is allowed to stand for aging and then dried to obtain a silver-doped lithium iron phosphate precursor; Step s2: stirring the silver-doped lithium iron phosphate precursor, glucose and deionized water, and then spray drying, sintering and cooling in the furnace to obtain carbon-coated silver-doped lithium iron phosphate; Step s3: stirring pyrrole, potassium tert-butoxide, 5-chloro-2-nitrotrifluorotoluene, and anhydrous ether to react. After the reaction, the reaction product is cooled and then poured into ice water. The organic phase is rotary evaporated, dried, and purified by silica gel column chromatography to obtain modified pyrrole; Step s4: Anhydrous ferric chloride and ethanol solution are stirred to react, and then carbon-coated silver-doped lithium iron phosphate and modified pyrrole are added and the stirring reaction is continued. After the reaction is completed, the reaction product is centrifuged, and the precipitate is washed and dried to obtain a double-layer coated silver-doped lithium iron phosphate.
2. The lithium iron phosphate material according to claim 1, characterized in that: The usage ratio of the lithium carbonate, ferric nitrate nonahydrate, ammonium dihydrogen phosphate, citric acid solution and silver nitrate in step s1 is 11-13 mmol:10 mmol:10 mmol:50-60 mL:0.1-0.5 g; the mass fraction of the citric acid solution is 3-5%.
3. The lithium iron phosphate material according to claim 1, characterized in that: The mass fraction of the ammonia water in step s1 is 20-25%.
4. The lithium iron phosphate material according to claim 1, characterized in that: The usage ratio of the silver-doped lithium iron phosphate precursor, glucose and deionized water in step s2 is 10 g: 1-7 g: 90-100 mL.
5. The lithium iron phosphate material according to claim 1, characterized in that: The usage ratio of the pyrrole, potassium tert-butoxide, 5-chloro-2-nitrotrifluorotoluene and anhydrous ether in step s3 is 10 mmol: 10 mmol: 10 mmol: 60-70 mL.
6. The lithium iron phosphate material according to claim 1, characterized in that: The usage ratio of the anhydrous ferric chloride, ethanol solution, carbon-coated silver-doped lithium iron phosphate and modified pyrrole in step s4 is 2.5-4.5 g: 70-80 mL: 5 g: 0.3-0.9 g.
7. The lithium iron phosphate material according to claim 1, characterized in that: The volume fraction of the ethanol solution in step s4 is 50-60%.
8. A method for preparing lithium iron phosphate material, characterized in that: The following steps are involved: Step 1: Weigh 8-10 parts of double-layer coated silver-doped lithium iron phosphate, 1-1.2 parts of binder, 1-1.5 parts of conductive agent and 15-17 parts of solvent according to weight and set aside; Step 2: Add the double-layer coated silver-doped lithium iron phosphate, a binder, a conductive agent and a solvent into a ball mill, and ball mill for 3-5 hours at a ball milling rate of 200-300 r / min to obtain a lithium iron phosphate material.
9. The method for preparing a lithium iron phosphate material according to claim 8, characterized in that: The solvent is N-methylpyrrolidone.
10. Use of the lithium iron phosphate material prepared by the method for preparing the lithium iron phosphate material according to any one of claims 8 to 9 in a positive electrode of a lithium ion battery.
Citation Information
Patent Citations
Preparation method for silver nano-sphere loaded LiFePO4 nano-fibers
CN102817107A
Method for improving electrochemical performance of LiFePO4 through polypyrrole / graphene
CN104966836A
Preparation method for porous nitrogen-doped graphene-similar carbon film coated lithium iron phosphate compound
CN106129358A
Method for preparing lithium iron phosphate cathode material by two-step solution method
CN108258237A
Preparation method for nano-porous lithium-rich lithium iron phosphate material
CN108923046A
Cited By
Lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof
CN120834151A
